Prediction of apolipoprotein A-I and high-density lipoprotein cholesterol in the neurological impairment and relapse of neuromyelitis optica spectrum disorder - Wang, Yanyan; Wang, Feng; Huang, Teng; Zeng, Ziling; Jiao, Li; Sun, Hao; Zhang, Xiaoyu; Wang, Baojie; Liu, Rujia; Guo, Shougang (Frontiers in Neuroscience, 2025)
Background and purposeNeuromyelitis Optica Spectrum Disorder (NMOSD) is a rare inflammatory demyelinating disorder of the central nervous system, frequently resulting in irreversible neurological deficits such as blindness and paralysis. Emerging evidence suggests that dyslipidemia is associated with increased disability and poorer outcomes in autoimmune diseases. The purpose of the study is to investigate the associations between lipid profile with neurological impairment and relapse.MethodsThis study retrospectively collected data from 130 hospitalized patients with AQP4-IgG positive NMOSD. Based on the Expanded Disability Status Scale (EDSS) scores at admission, patients were categorized into a mild-to-moderate group (EDSS ≤ 5.5) and a severe group (EDSS ≥ 6). All included patients were followed for at least 1 year, and were further divided into relapse and non-relapse groups based on whether a relapse occurred during the follow-up period. Logistic regression analysis was used to identify independent risk factors associated with the severity of neurological impairment and relapse. Receiver operating characteristic (ROC) curve analysis was conducted to determine the cutoff value of apolipoprotein A-I (ApoA-I) in predicting severe neurological impairment. Spearman correlation analysis was performed to assess the relationships among ApoA-I, high-density lipoprotein cholesterol (HDL-C) and CRP.ResultsMultivariate binary logistic regression analysis revealed that ApoA-I (OR = 0.138, 95% CI: 0.021–0.902, p = 0.039) and the number of spinal cord lesion segments (OR = 1.368, 95% CI: 1.181–1.584, p < 0.001) were independent risk factors for the severity of neurological impairment. The area under the ROC curve (AUC) for ApoA-I in predicting the severity of neurological impairment was 0.647 (95% CI: 0.542–0.751), with a cutoff value of 1.165, a sensitivity of 59.4%, and a specificity of 67.6%. Multivariate logistic regression analysis identified HDL-C (OR = 0.082, 95% CI: 0.008–0.847, p = 0.036), clinical phenotype—specifically, compared to optic neuritis, myelitis (OR = 0.130, 95% CI: 0.037–0.458, p = 0.002), brainstem/cerebral syndrome (OR = 0.070, 95% CI: 0.007–0.731, p = 0.026), and mixed phenotypes (OR = 0.107, 95% CI: 0.018–0.642, p = 0.014) —as well as the use of subsequent monoclonal antibody therapy (OR = 0.190, 95% CI: 0.045–0.799, p = 0.023) as independent protective factors against relapse. Spearman correlation analysis showed that ApoA-I and HDL-C were significantly negatively correlated with CRP (r = −0.230, p = 0.008; r = −0.310, p < 0.001, respectively).ConclusionReduced levels of ApoA-I and HDL-C were associated with more severe neurological deficits and an increased risk of relapse.